The impact of Covid-19 lockdown on socio-economic activities in Kaduna State, Nigeria - Muhammed, Abdulkadir Yahaya; Adenike, Montiliat; Salahudeen, Hajara (Goodwood Publishing, 2020)
Purpose: Coronavirus (Covid-19) pandemic affects social and economic activities all over the world. This study analyses the impact of lockdown caused by the pandemic in Kaduna State, Nigeria, so that the public can appreciate it and take adequate measures to curb it. Research methodology: A total of 370 questionnaires were administered to traders, worshippers, parents and marketers. The interview was also conducted in mosques and churches, markets and houses to collect data during and after the Covid-19 lockdown. The data were collected within a month from Tuesday 21 May 2020 to 21 June 2020. Results: The results reveal that 67% of the respondents see commercial activities doing well before the lockdown, but only 12% during the lockdown and a further 59% after the lockdown. The results also reveal that 56% of the respondents see educational acquisitions doing well before the lockdown, 13% during and 24% after the lockdown. The results further show that 60%, 10% and 53% were for before, during and after the lockdown, respectively, for religious activities. Limitation: The data was not collected before the lockdown but only during and after. This might not give highly reliable data for one of the data was organised not at the exact time of the incidence. Contribution: The study will help both public and private organisations appreciate the difficulties caused by the lockdown in the state so as to find alternative ways of cubbing the pandemic subsequently. The study can also be replicated in some areas with similar characteristics. Keywords: Impact, Covid-19, Lockdown, Socio-economic activities